2019
DOI: 10.3390/su11113044
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Efficiency of Organic and Conventional Cotton in Benin

Abstract: Recent years have seen an increasing awareness of the relative advantage of organic and conventional agriculture. This study aims to analyze the environmental efficiency of organic and conventional cotton in Benin. A Translog hyperbolic distance function which allows us to consider the joint production of desirable and undesirable output is used to analyze the environmental efficiency among organic and conventional cotton production farmers. The model includes factors that affect environmental efficiency. Gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The production of 4,750 kg of cotton from 1 ha requires 29,138.11 MJ energy (75.5% from fuel and fertilizer). Bonou-zin et al (2019) studied energy flow and environmental emissions from cotton cultivations at conventional and organic farms. Organic farmers consumed less energy than conventional farmers; similarly, the quantity of GHG emission produced by organic farmers is relatively lower than the conventional farmers, but organic farmers are still environmentally inefficient compared to conventional farmers.…”
Section: Introductionmentioning
confidence: 99%
“…The production of 4,750 kg of cotton from 1 ha requires 29,138.11 MJ energy (75.5% from fuel and fertilizer). Bonou-zin et al (2019) studied energy flow and environmental emissions from cotton cultivations at conventional and organic farms. Organic farmers consumed less energy than conventional farmers; similarly, the quantity of GHG emission produced by organic farmers is relatively lower than the conventional farmers, but organic farmers are still environmentally inefficient compared to conventional farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Although chemical fertilizers can increase crop yields quickly, they can also reduce soil fertility after a long period of application. Recent studies have indicated that the excessive use of chemical fertilizers cause harmful effects on the soil chemical, physical and biological properties, which lead to the degradation of its natural fertility (Prashar and Shah, 2016;Bonou-zin et al, 2019). From an environmental point of view, organic fertilizers improve soil structure by creating more air space and increasing soil water retention.…”
Section: Discussionmentioning
confidence: 99%
“…The competitiveness and increased food demand have transformed conventional agriculture toward modern agricultural systems through the use of synthetic inputs like increased use of fertilizers, and pesticides to get higher yields instead of following eco-friendly techniques (organic manuring, precision farming, fallowing, crop rotation). The agricultural sector is considered as one of the major sectors to contribute to GHG emissions, and due to increased deforestation and excessive use of synthetic inputs (pesticides, fertilizers), emissions in agriculture have been increased by 13.5% ( Lenka et al, 2015 ; Bonou-zin et al, 2019 ). Embezzled and excessive use of synthetic N-fertilizers for higher productivity and to ensure food security consequently leads to increased nitrous oxide (N 2 O) emissions ( Shcherbak et al, 2014 ; Griffis et al, 2017 ).…”
Section: Climate Change Impacts On Key Components Of Food Securitymentioning
confidence: 99%